Serotonin and norepinephrine reuptake inhibitors antidepressant use is related to lower baroreflex sensitivity independently of the severity of depressive symptoms. A community-study of 9213 participants from the Paris Prospective Study III. (August 2016) - Empana, Jean-Philippe; Prugger, Christof; Thomas, Frédérique; Perier, Marie-Cécile; Zanoli, Luca; Castiglioni, Paolo; Guibout, Catherine; Causeret, Sophie; Barnes, Caroline; Lemogne, Cédric; Parati, Gianfranco; Laurent, Stéphane; et al.
Abstract: Background and aims: We assess the respective relationship of high depressive symptoms and antidepressant use (ATD) with baroreflex sensitivity (BRS) in subjects from the community who enrolled the Paris Prospective Study III. Methods: Recruitment took place in a large health preventive centre in Paris (France), between May 2008 and June 2012. BRS was investigated by spectral analysis of the spontaneous carotid distension rate and RR intervals using non-invasive high-resolution ultrasound carotid-echotracking. A total score ≥7 on a 13-item standardized questionnaire defined the presence of high depressive symptoms. Information on ATD use was obtained on a face-to-face interview with a medical doctor who checked the most recent medical prescriptions and/or medical package. Results: There were 9213 participants aged 50–75 years (38.6% of women), including 5.6% with high-depressive symptoms and 5.2% on ATD. High depressive symptoms were not associated with low BRS (below the median) even in unadjusted logistic regression analysis (OR = 1.09; 95%CI: 0.91–1.30). Instead, ATD use was related to low BRS in multivariate logistic regression analysis (OR = 1.27; 95% CI: 1.04–1.54). This association remains after adjusting for and matching on propensity score of receiving ATD. A specific association with serotonin and norepinephrine reuptake inhibitors was observed (OR = 1.94; 95% CI: 1.16–3.22). Conclusions: ATD use and serotonin and norepinephrine reuptake inhibitors in particular, but not high depressive symptoms, is associated with low BRS. If confirmed, these results may bring novel insights into the mechanisms linking depressive symptoms and/or ATD use with cardiovascular disease onset. Graphical abstract: Multivariate odds ratios of antidepressants use for low baroreflex sensitivity. The Paris Prospective study III. Highlights: Serotonin and norepinephrine reuptake inhibitors antidepressants use was associated with low baroreflex sensitivity. The effect size was equivalent to the effect of 8 years of ageing, underlying the clinical relevance of the study results. This may identifiy a disease process linking depressive symptoms and/or antidepressant use with cardiovascular disease.